NURSES' KNOWLEDGE OF EVIDENCE-BASED GUIDELINES FOR PREVENTION OF VENTILATOR-ASSOCIATED PNEUMONIA IN CRITICAL CARE AREAS: A PRE AND POST TEST DESIGN - Meherali, Salima Moez; Parpio, Yasmin; Ali, Tazeen S.; Javed, Fawad (Journal of Ayub Medical College Abbottabad, 2011)
Background: Ventilator associated pneumonia (VAP) is a common hospital acquired pneumonia in ventilated patients. VAP is associated with increased morbidity, mortality duration of hospitalization and cost of treatment. Critical care nurses are usually unaware of evidence based preventive guidelines for VAP, resulting in negative impact on all aspects of patient care. This study investigated the impact of a 5-hour teaching module on nurses' knowledge to practice evidence based guidelines for the prevention of VAP. Methods: This study was conducted at a private tertiary care teaching hospital in Karachi, Pakistan. Single group pre-test post-test design was used. Forty nurses were included in the study. The knowledge of nurses was assessed before, immediately after and 4 weeks after the intervention. The final sample (n=40) was selected on the basis of the set inclusion criteria. The demographic data sheet was used to collect relevant information about the participants. Knowledge was assessed through a self-developed validated tool, consisting of multiple choice questions. The difference in knowledge was analysed through repeated measures of analysis of variance. The mean scores at 3 time points were compared using the Tukey's multiple comparison procedure. Results: Knowledge scores of participants increased significantly after the educational intervention in the first post-test; however, there was a decline in the score in post-test 2. Conclusion: The 5-hour teaching module significantly enhanced nurses' knowledge towards evidence based guidelines for the prevention of VAP. Further research is needed to assess the impact of training on nursing practice and to explore factors affecting attitudinal change. Keywords: Critical care, Pneumonia, Ventilator associated pneumonia, evidence based practice, nurses' knowledge